Neoatherosclerosis in the stent - A. A. Komkov; V. P. Mazaev; S. V. Ryazanova (Столичная издательская компания, 2015)
Achievements of interventional cardiology in the treatment of coronary artery disease are based on coronary balloon angioplasty with implanting bare metal stents and drug eluting stents. Questions of complications such as early stent thrombosis and restenosis of stent were solved in a considerable degree. However, with the lengthening of the followup period, the problem of late complications became obvious. Except endothelization and fibromuscular proliferation in stented coronary arteries the process of plaque formation has an important influence on later complications in follow-up period more than one year. This process was defined as neoatherosclerosis. This is verified by clinical manifestations of the disease, histological studies, angioscopy, intravascular ultrasound and optical-coherence tomography in stented patients. Dynamic observation of the condition in stentedcoronary arteries showed multistep proliferation with restenosis, its regression, and neoatherosclerosis development. Evidences of neoatherosclerosis formation in stented coronary arteries are considered in this review.